-4(m+1)=-2(m+7)

Simple and best practice solution for -4(m+1)=-2(m+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(m+1)=-2(m+7) equation:


Simplifying
-4(m + 1) = -2(m + 7)

Reorder the terms:
-4(1 + m) = -2(m + 7)
(1 * -4 + m * -4) = -2(m + 7)
(-4 + -4m) = -2(m + 7)

Reorder the terms:
-4 + -4m = -2(7 + m)
-4 + -4m = (7 * -2 + m * -2)
-4 + -4m = (-14 + -2m)

Solving
-4 + -4m = -14 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
-4 + -4m + 2m = -14 + -2m + 2m

Combine like terms: -4m + 2m = -2m
-4 + -2m = -14 + -2m + 2m

Combine like terms: -2m + 2m = 0
-4 + -2m = -14 + 0
-4 + -2m = -14

Add '4' to each side of the equation.
-4 + 4 + -2m = -14 + 4

Combine like terms: -4 + 4 = 0
0 + -2m = -14 + 4
-2m = -14 + 4

Combine like terms: -14 + 4 = -10
-2m = -10

Divide each side by '-2'.
m = 5

Simplifying
m = 5

See similar equations:

| 10+9-c=-9+3c | | 5-2*7/2 | | -7-7q=-7-9q | | n/8+4=6 | | 5b^2-34b+24=0 | | x/12=8 | | 5-2*-7/2 | | n/2+4=6 | | 6+d=-10-d | | 17-63= | | x^3-8x^2+4x-32=0 | | n/8+5=10 | | -5-2v=-7v | | 3x+3x+3x=198 | | 6(5-4r)=6(4-5r) | | (4/(x+4))-(3/(x-4))=(2x/((x^2)-16)) | | 10+5v=7v-10 | | 6s+5s=-77 | | -g=g+8 | | -5-3y=-18 | | 8h+8=-2+10h | | 7b-5=2b-.5 | | x^3+4x^2-32x=128 | | x/10-2=4 | | -6r=9-7r | | y/17=-5 | | x+5x+(35+x)=385 | | -7=x/4+(-5) | | 2u^2=7u+4 | | 150-1/2= | | 1/6(2x-4)=7 | | 3v^2+9v+4= |

Equations solver categories